Introducing Autodesk Revit Architecture 2011 - Davis, Pat, 1968-; Davis, Patrick (Hoboken, N.J. : Wiley Pub., 2010)
'Revit all-stars present a fast, focused introduction to Revit functions, tools, and concepts. Hailed for its ease of use, power, and sophistication, Revit is the industry-leading Building Information Modeling (BIM) software package. Introducing Revit Architecture provides a thorough overview of Revit's concepts, interface conventions, tools, and tasks. In-depth discussions, reinforced by comprehensive step-by-step exercises, detail how to model, document, present, and share designs. Written by expert authors - all architects with years of Revit experience - Introducing Revit Architecture is the perfect resource for readers of all skill levels who want to quickly accomplish crucial Revit tasks. Practical exercises on core Revit features enable new users to quickly get up to speed A 16-page color insert focusing on real-world Revit uses drawn from the team's experience and industry contacts Straightforward explanations, real-world examples, beautiful illustrations, and practical tutorials focus squarely on accomplishing vital Revit tasks Introducing Revit Architecture helps professionals and students to easily and efficiently learn the basics of Revit and BIM.'--
Includes index.
Keywords: Autodesk Revit; Architectural drawing -- Computer-aided design; Architectural design -- Data processing